2022
DOI: 10.1038/s41598-022-16080-y
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF derived from the inflammatory microenvironment potentially enhanced PD-L1 expression on tumor-associated macrophages in human breast cancer

Abstract: Ever since immune checkpoint inhibitors have been approved for anti-cancer therapy in several cancers, including triple-negative breast cancer, the significance of programmed death-1 ligand 1 (PD-L1) expression in the tumor immune microenvironment has been a topic of interest. In the present study, we investigated the detailed mechanisms of PD-L1 overexpression on tumor-associated macrophages (TAMs) in breast cancer. In in vitro culture studies using human monocyte-derived macrophages, lymphocytes, and breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…40 A number of signaling pathways, including NF-κB and STAT pathways, are involved in PD-L1 expression. 29,30 In the current study, we found that the ERK signaling pathway was associated with PD-L1 expression in macrophages following MFC-exo treatment. After inhibiting the ERK signaling pathway, PD-L1 expression was significantly decreased in macrophages after MFC-exo stimulation.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…40 A number of signaling pathways, including NF-κB and STAT pathways, are involved in PD-L1 expression. 29,30 In the current study, we found that the ERK signaling pathway was associated with PD-L1 expression in macrophages following MFC-exo treatment. After inhibiting the ERK signaling pathway, PD-L1 expression was significantly decreased in macrophages after MFC-exo stimulation.…”
Section: Discussionsupporting
confidence: 51%
“…PD‐L1 expression is mediated by genomic alterations, epigenetic modifications, transcriptional regulation, and posttranscriptional regulation and modification 40 . A number of signaling pathways, including NF‐κB and STAT pathways, are involved in PD‐L1 expression 29,30 . In the current study, we found that the ERK signaling pathway was associated with PD‐L1 expression in macrophages following MFC‐exo treatment.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Anti-GM-CSF therapy also inhibited the maturation and differentiation of TAMs. However, anti-GM-CSF therapy was ineffective against an E0771 breast cancer model [ 85 ]. This discrepancy might have been due to GM-CSF expression in tumor cells, since LLC cells express high levels of GM-CSF, whereas E0771 expresses no GM-CSF.…”
Section: Potential Immunotherapy Against Gm-csfmentioning
confidence: 99%